2016
DOI: 10.1002/2016jb013105
|View full text |Cite
|
Sign up to set email alerts
|

New perspectives on self‐similarity for shallow thrust earthquakes

Abstract: Scaling of dynamic rupture processes from small to large earthquakes is critical to seismic hazard assessment. Large subduction earthquakes are typically remote, and we mostly rely on teleseismic body waves to extract information on their slip rate functions. We estimate the P wave source spectra of 942 thrust earthquakes of magnitude Mw 5.5 and above by carefully removing wave propagation effects (geometrical spreading, attenuation, and free surface effects). The conventional spectral model of a single‐corner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
116
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 112 publications
(133 citation statements)
references
References 98 publications
17
116
0
Order By: Relevance
“…They also found along-strike variations, in particular, very low values along portions of the Central America subduction zone and near the hypocenter of the 2004 Sumatra earthquake. Similar to the depth dependence of source duration discussed in the "Source Duration" subsection herein, Denolle and Shearer (2016) found very weak depth dependence for stress drop and scaled energy using their global catalog. They observed regional variations, with lower stress drop in general in western Pacific subduction zones as compared to eastern Pacific zones, and very low stress drops for earthquakes along the Alaska-Aleutian subduction zone.…”
Section: Bilek and Lay | Subduction Zone Megathrust Earthquakes Geospsupporting
confidence: 70%
See 2 more Smart Citations
“…They also found along-strike variations, in particular, very low values along portions of the Central America subduction zone and near the hypocenter of the 2004 Sumatra earthquake. Similar to the depth dependence of source duration discussed in the "Source Duration" subsection herein, Denolle and Shearer (2016) found very weak depth dependence for stress drop and scaled energy using their global catalog. They observed regional variations, with lower stress drop in general in western Pacific subduction zones as compared to eastern Pacific zones, and very low stress drops for earthquakes along the Alaska-Aleutian subduction zone.…”
Section: Bilek and Lay | Subduction Zone Megathrust Earthquakes Geospsupporting
confidence: 70%
“…Denolle and Shearer (2016) examined spectral ratios for over 900 thrust earthquakes (M > 5.5) and found weak dependence of scaled source duration with increasing depth on the fault. Similarly, Ye et al (2016c) found longer-duration earthquakes in the shallowest (<18 km) portion of the subduction megathrust using finite fault determinations for over 100 M w > 7 earthquakes.…”
Section: Source Durationmentioning
confidence: 99%
See 1 more Smart Citation
“…72 earthquakes (over 90) correspond to ruptures with impulsivity and scaled energy below the depth‐varying averages (Figures and ). Based on teleseismic source spectra analysis, Denolle and Shearer () also report low values of stress drop and radiated energy in this subduction zone, with a similar increase when approaching the Solomon Islands. ERM0 values are lower than expected by Fms values, which indicates that ruptures have simple time history ( C ind ≤2 for 68 earthquakes over 90).…”
Section: Differences Among the Subduction Zones And Relations With Sumentioning
confidence: 87%
“…The most classical one is the corner frequency f c of the seismic spectrum, which can be related to the stress drop Δ σ when assuming a simple source model with constant rupture velocity (e.g., Brune, ; Madariaga, ). Systematic analyses of the corner frequency have been done both at the local scale (Prejean & Ellsworth, ; Uchide et al, , for instance) and at the global scale (e.g., Allmann & Shearer, , and more recently Denolle & Shearer, ).…”
Section: Introductionmentioning
confidence: 99%